Genomic organization of mouse and human Bruton's agammaglobulinemia tyrosine kinase (Btk) loci. - Sideras, P; Müller, S; Shiels, H; Jin, H; Khan, W; Nilsson, L; Parkinson, E; Thomas, J; Brandén, L; Larsson, I (1994)
Btk is a cytoplasmic protein tyrosine kinase (PTK) that has been directly implicated in the pathogenesis of X-linked agammaglobulinaemia (XLA) in humans and X-linked immunodeficiency (Xid) in mice. We have isolated phage and cosmid clones that allowed us to deduce the genomic structure of mouse and human Btk loci. The mouse and human genes are contained within genomic regions that span approximately 43.5 kb and 37.5 kb, respectively. Both loci contain 18 coding exons ranging between 55 and 560 bp in size with introns ranging in size from 164 bp to approximately 9 kb. The 5'-untranslated regions are encoded by single exons located approximately 9 kb upstream of the first coding exon. Exon 18 encodes for the last 23 carboxyl-terminal amino acids and the entire 3'-untranslated region. The location of intron/exon boundaries in the catalytic domains of the mouse and human Btk loci differs from that found in other described sub-families of intracellular PTKs, namely that of Src, Fes/Fer, Csk, and Abl/Arg. This observation is consistent with the classification of Btk together with the recently characterized kinases, Tec and Itk, into a separate sub-family of cytoplasmic PTKs. Putative transcription initiation sites in the mouse and human Btk loci have been determined by using the rapid amplification of cDNA ends assay. Similar to many other PTK specific genes, the putative Btk promoters lack obvious TATAA and CAAAT motifs. Putative initiator elements and potential binding sites for Ets (PEA-3), zeste, and PuF transcription factors are located within the 300 bp which are located upstream of the major transcription start site in both species. These sequences can mediate promoter activity when placed upstream of a promotorless chloramphenicol acetyl transferase reporter gene in an orientation-dependent manner. The present analysis will significantly facilitate the mutational analyses of patients with XLA and the further characterization of the function and regulation of the Btk molecule.